ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA SITUS JUAL-BELI ONLINE - I Gede Andri Setiawan; Sukardi Sukardi (Universitas Ahmad Dahlan, 2016)
The purpose of this study were to analyze (1) the influence of trust of the purchase interest of online shop consumers, (2) the influence of risk perception of the purchase interest of online shop consumers, (3) the influence of use fulness perception of the purchase interest of online shop consumers, (4) the influence of price perception of the purchase interest of online shop consumers. The populations in this research are student of Ahmad Dahlah University Yogyakarta Campus One. The method sample is purposif sampling with the number of sample as much as 100 respondents from three Faculty that is, Economy Faculty, Psycology Faculty, and FTDI. Collecting data using questionnaires that was done validity test and realibity test. This research was done by using multiple linear regression data analysis. The results of this study indicate that (1) the trust is not significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant value is bigger than the probability alpha value of 0.05 (0,206 > 0.05), and the regression coefficient has a positive value of 0.062; (2) the trust is not significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant value is bigger than the probability alpha value of 0.05 (0, 0,234 > 0.05), and the regression coefficient has a positive value of 0.057; (3) the usefulness perception is significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant value is smaller than the probability alpha value of 0.05 (0.000 < 0.05), and the regression coefficients has a positive value of 0.456; (4) the price perception is not significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant value is bigger than the probability alpha value of 0.05 (0.066 > 0.05), and the regression coefficient has a positive value of 0.111; and (5) trust, risk perception, usefulness perception and price perception together have an effect on consumer purchase interest of the sites online shop, this is evidenced by the significant value is smaller than the probability alpha value of 0.05 (0.000 < 0.05). The R2 test results in this study was obtained R2 value of 0.413. This shows that purchase interest is influenced by trust, risk perception, use perception, and price perception by 41.3%, while the remaining 58.7% is influenced by other factors not observed by the researcher or considered fixed.